Analisis Sistem Informasi Penggajian Buruh Berbasis Android Pada Mitra Indo Agro - Riska Puspitasari; Wakhdan Wakhdan; Anna Probowati (Prospect : Jurnal Manajemen dan Akuntansi, 2024)
This study aims to examine and evaluate the results of the implementation of an android-based labor payroll system. The purpose of this research is to find out the description of the system, application implementation, problems, and solutions on android-based payroll at Mitra Indo Agro. The results of the study obtained are used to evaluate the factors and parts of the payroll system for this android-based application that needs to be improved. This study uses a qualitative descriptive research method. Determination of informants using snowball sampling technique where the research subjects as many as 4 employees who are directly related to the android-based payroll process. Data collection techniques are through field studies consisting of interviews, observations, documentation, and literature studies. Data analysis techniques through data reduction steps, data exposure, data interpretation and drawing conclusions. The data validation technique uses source triangulation. The data presentation technique uses a program flow (flowchart) and fishbone diagrams (fish bones). The results of the research have shown that the Android-based GajiQ system helps provide large databases with the CRUD (Create, Read, Update, Delete) method, automate reports such as attendance recap, salary calculations, payroll history reports and make it easier to find labor data. The implementation of the Android-based GajiQ application can be a new medium of choice for companies to manage payroll in real time, quickly, and accurately that does not involve many parties in making payroll, payments, and payroll procedures. Problems found by the system are still bugs or crashes, error messages such as app force close appear.